Byte-Sized Finance, Bushel-Sized Benefits: unraveling digital financial inclusion impact on China’s agricultural green development - Zhang, Ludan; Qi, Yanbin; Deng, Xin (Frontiers in Environmental Science, 2024)
China's rural financial landscape has long been characterized by exclusion, leaving countless farmers without access to essential financial services. However, the advent of digital financial inclusion presents a promising solution, offering low-cost, high-penetration avenues to bolster agricultural sustainability. This paper unravels how "Byte-Sized Finance" can yield "Bushel-Sized Benefits" in China's agricultural green development. Methodologically, we pioneer a novel system to gauge agricultural green development across 31 Chinese provinces spanning from 2013 to 2021.Empirically, employing fixed-effect, mediation effect, and spatial Durbin models, our study reveals the intricate pathways through which digital financial inclusion influences agricultural green development. We find that it exerts its impact through the lenses of industrial structure and entrepreneurship, operating at both macro and micro levels. Furthermore, our analysis uncovers spatial spillover effects, shedding light on the differential roles played by these mechanisms across regions. This groundbreaking discovery underscores the transformative potential of leveraging digital financial inclusion to propel China toward agricultural green development. By shedding light on these crucial dynamics, our findings offer insights for policymakers, researchers, and practitioners striving to foster sustainability within China's agricultural sector. * t statistics in parentheses；*p<0.1, **p<0.05, ***p<0.01Table 10. Instrumental variables regression. * t statistics in parentheses；*p<0.1, **p<0.05, ***p<0.01